The Urgency of Understanding Underage Marriage Law Due to Out of Wedlock Pregnancy for Students - Budiman, Budiman; Rahmawati, Rahmawati; Fikri, Fikri; Aris, Aris; Akhsan, Muhammad (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study discusses the importance of strengthening the legal understanding of underage marriage due to pregnancy out of wedlock for students in Parepare City. Consisting of two problems: what is the context of the impact of changes in the marriage age law due to pregnancy out of wedlock, and what is the reaction to the rejection of child marriage due to pregnancy out of wedlock for students in Parepare City? The research method is field research through a qualitative descriptive approach. This study uses data analysis with theories of legal change and social inequality. The results showed that students generally understand the context of the impact of changes in marriage age law to protect against the occurrence of underage marriage due to pregnancy out of wedlock with a very high risk. The reaction to the rejection of underage marriage due to extramarital pregnancy has built a paradigm to protect the rights and welfare of children, prevent forced marriage, and avoid adverse health and social risks.